"Made Known in the Breaking of the Bread: Accompaniment and the Practice of Medicine". (August 2021) - Nicholson, C. Phifer
Accompaniment is a term drawn from Catholic social teaching that is used by secular organizations, such as Partners in Health and Health for Palestine, to frame their work for health justice in solidarity with the world's poor. Through an exploration of the Emmaus story from Luke's Gospel, this article seeks to frame medicine itself as a practice of accompaniment of the sick and, in particular, the sick poor. Medicine as accompaniment requires healers to draw near to, walk alongside, and break bread with the sick. This way of practicing medicine has implications for which communities clinicians preferentially accompany, where clinicians live, how they spend their time and money, and what rewards they seek from the practice of medicine. Medicine as accompaniment is a contemplative practice, a journey on which one comes to experience authentic communion with both God and neighbor.